Inhibitory effect of phytochemicals on Candida albicans biofilms on denture liners surfaces (Research, Society and Development, 2020)
Objective: To evaluate in vitro antimicrobial activity of a-terpineol, cinnamaldehyde, 1% sodium hypochlorite, 0,12% chlorhexidine, and corega® in biofilm of Candida albicans (ATCC 90028) developed on soft prosthetic resurfacing surfaces. Methodology: Specimens from the Bosworth Trusoft (Bosworth Company- USA) material were made according to the manufacturer's instructions and the formation of the artificial salivary film was induced for 60 minutes at 37 ° C. The biofilm was seeded (1x106 CFU/mL) and, after initial adhesion (24h, 37°C), exposed to a-terpineol (10 mg/mL), cinnamaldehyde (10 mg/mL), 1% sodium hypochlorite, chlorhexidine 0,12%, corega and saline (growth control). The specimens remained for 1 or 10 minutes, in each solution, with exposures made 24h, 48h and 72h after sowing the biofilm. Metabolic activity was evaluated by the MTT test and Shore A hardness, using a microdurometer. The statistical analysis was performed using the Kruskal-Wallis/ Mann Whitney tests and the t test (α = 5%). Results: It was observed that for exposure for 1 min, cinnamaldehyde, chlorhexidine and hypochlorite were efficient (p> 0,05). At 10 minutes, a-terpineol showed activity similar to growth control (p> 0,05), differing from other substances. Regarding hardness, there was no difference between groups, only for sodium hypochlorite and corega. Conclusion: Cinnamaldehyde, chlorhexidine and hypochlorite demonstrated antifungal activity on Candida albicans biofilm on prosthetic resurfacing surface.